2014
DOI: 10.1590/s1982-56762014000600002
|View full text |Cite
|
Sign up to set email alerts
|

Favorable conditions for Xanthomonas axonopodis infection in Eucalyptus spp.

Abstract: Currently, Xanthomonas axonopodis is one of the main foliar pathogens for Eucalyptus spp. in Brazil. It induces leaf blight and defoliation of seedlings in the nursery and young plants in the field. However, little is known about the favorable conditions for infection. The establishment and development of bacterial leaf blight caused by X. axonopodis in eucalyptus was studied for different leaf ages, temperatures and leaf wetness durations. Disease severity increased with leaf age, and the highest severity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…Diseased eucalypt cuttings are unsuitable for planting in the field due to the reduced photosynthetic area and potential for the spread of the pathogen into previously unaffected areas (Neves, Guimarães, Ferraz, & Alfenas, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Diseased eucalypt cuttings are unsuitable for planting in the field due to the reduced photosynthetic area and potential for the spread of the pathogen into previously unaffected areas (Neves, Guimarães, Ferraz, & Alfenas, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, incidence and severity of symptoms caused by bacteria rise with increasing temperatures [30,31]. According to Neves et al [17], the optimum temperature range for development of bacterial leaf blight in eucalyptus is between 26 and 30 • C.…”
Section: Discussionmentioning
confidence: 95%
“…Foliar bacterial diseases are pathosystems polycyclic, in which the bacterial spreads between leaves and plants, mainly by water splash [15,16]. Several other studies with bacterial diseases have shown the above-mentioned models as a better fit for pathogen incidence data, both in the nursery and in the field [15,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations